On-column reaction set-up for high-throughput screenings and mechanistic investigations - Stockinger, Skrollan Carina; Troendlin, Johannes; Rominger, Frank; Trapp, Oliver (Advanced synthesis & catalysis, 2015)
A screening platform, which offers a high-throughput approach as well as an easy investigation of kinetic isotope effects, applicable to a wide range of reactions is presented. To illustrate the high potential of this approach, the asymmetric transfer hydrogenation of methyl benzoylformate with copper(II) bis(oxazoline) and Hantzsch ester was examined. Accordingly, the enantioselectivities of the reaction performed on-column in a microcapillary were comparable to standard reaction conditions, however, we were able achieve catalysis and analysis in a single step in less than 30 min. The throughput can be increased by simultaneous investigation of different substrates without increasing the overall analysis time. Use of di-deuterated Hantzsch ester allowed us to investigate the kinetic isotope effect of the transfer hydrogenation reaction only requiring a minute amount of the deuterated transfer hydrogenation reagent. Hence we were able to get further insights into the mechanism of the asymmetric transfer hydrogenation using Hantzsch ester as hydrogen source. The here presented technique is broadly applicable to study isotope effects on a very small scale, which is a rapid and an inexpensive alternative compared to conventional experiments.
Gesehen am 23.06.2020